2013
DOI: 10.1007/s00436-013-3308-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infection by larvae of Angiostrongylus cantonensis (Nematoda, Metastrongylidae) on the lipid metabolism of the experimental intermediate host Biomphalaria glabrata (Mollusca: Gastropoda)

Abstract: Experimental infection of Biomphalaria glabrata by Angiostrongylus cantonensis induces significant changes in the concentrations of triacylglycerol and cholesterol in the hemolymph and of neutral lipids in the digestive gonad-gland (DGG) complex of the host snail. In this study, snails were dissected after 1, 2, and 3 weeks of infection to collect the hemolymph and DGG and to measure the levels of cholesterol and triacylglycerol in the hemolymph and neutral lipid fractions in the tissues. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Tunholi et al, 2011;Tunholi-Alves et al, 2012;Tunholi-Alves et al, 2013;Alves et al, 2014). TunholiI- presented similar results in their study on the infection of Biomphalaria glabrata by Echinostoma paraensei.…”
supporting
confidence: 55%
“…Tunholi et al, 2011;Tunholi-Alves et al, 2012;Tunholi-Alves et al, 2013;Alves et al, 2014). TunholiI- presented similar results in their study on the infection of Biomphalaria glabrata by Echinostoma paraensei.…”
supporting
confidence: 55%
“…In the histopathological evaluation of the snails in the control group, there were no alterations (Figure S3 supplementary material); In addition, the presence of glycogen was strongly marked by PAS staining, as shown in images A and C. On the other hand, in snails exposed to H. bacteriophora HP88, alterations mainly established in the digestive gland were observed (Figure S3D supplementary material), characterized by the weak presence of glycogen, multifocal vacuolation and cell lysis. Tunholi-Alves et al (2013) reported that A. cantonensis infection also induced important histological changes in the digestive gland of B. glabrata. According to the authors, the organ in question has a remarkable ability to synthesize glycogen, proteins and lipids, providing in abundance essential nutrients for the evolution of the larval stages of the nematode, representing the main site of parasitic development.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, snails exposed for 24h were able to restore their glucose concentrations to levels similar to those of the control in the third week of analysis, thus suggesting the existence of homeostatic mechanisms involved in the control of glucose, denoting the ability of these hosts to adapt to this physiological stress condition. Such metabolic plasticity was described by Thompson & Lee (1986) in the B. glabrata/Schistosoma mansoni interface and by Tunholi-Alves et al (2013) studying the relationship between B. glabrata and A. cantonensis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now epidemic in a very wide region of the world, including Asia, the Pacific Islands, the Caribbean islands and Brazil. During the past decade, more than 2,800 cases of human infections and several human angiostrongyliasis outbreaks have been reported and which declared it as a public health problem that cannot be neglected [1].…”
Section: Introductionmentioning
confidence: 99%